Izpeljava slovanskih glagolov iz primerniških podstav - Šivic-Dular, Alenka (Slavistična revija, 1986)
Slavic verbs derived from the bases of comparative degrees of adjectives are classified into three groups: (i) derivatives from the short suppletive comparative-form base; (ii) derivatives from the short nonsuppletive comparative-form base; (iii) derivatives from the oblique-case comparative-form base.
Keywords: besedotvorje; glagol; pridevnik; slovanski jeziki